Community Empowerment Program in Pinogu Subdistrict, Bone Bolango Regency, Gorontalo Province, Indonesia: Concerning to The Unique Local Biodiversity Conservation - Retno Peni Sancayaningsih; Edi Suryanto (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
First year of three year plan of Community Empowerment Program through Student Community Services (SCS) of Gadjah Mada University was conducted in Pinogu Subdistrict, Bone Bolango Regency, Gorontalo Province in 2013. Pinogu is located on top of hill and reserved as the National Park of Bogani Nani Wartabone and this protects some endangered species, such as Tarsiers and Megapodon birds. As the most remote area, Pinogu had not been touched equally by the central government, therefore it was less developed. Pinogu had been popular with coffee plantations since Dutch colonial periods. This plantations was now too old and became forest. This SCS Program was designed to empowered local people for agribusiness including rejuvenate coffee plantation and coffee production and to educate local people to be aware of local biodiversity and understand how to conserve the most endangered species, Tarsiers and Maleo. Twenty one of UGM students from different study programs had been coached and trained priorly by Field Instructure within 3 months with the SCS-thematic programs and leadership; then they were mobilized to Pinogu and stayed for 2 months conducting the program. Two main programs out of 7 SCS thematic programs were successfully conducted during SCS activity in Pinogu, Bone Bolango Regency. Coffee agribusiness programs from up stream to down stream processes were trained to local community who interested in coffee production twice a week by students and biodiversity conservation was tought to junior high school students. These SCS program achievements were including establishment of anursary, improvement of local people skills in manage coffee plantation, selection of mature seed, seed drying, and good coffee processing, and also establishment of a coffee producing community. Conservation education on local endemic and endangered species—Megapodon birds (M. Maleo) and Tarsiers (T. Spectrum)—to junior high school students was attracting some students who were really interested in learning more about fauna conservation and improve student awareness on endemic and endangered species as the main icon for foreign tourists who visited Bone Bolango. The success of the SCS-UGM programs were contributed by sinergy of university and the local government financial support and students and field instructure commitment.